2023
DOI: 10.1002/advs.202301806
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxides: A Novel Promising 2D Nanomaterial for Bone Diseases Treatment

Abstract: Bone diseases including bone defects, bone infections, osteoarthritis, and bone tumors seriously affect life quality of the patient and bring serious economic burdens to social health management, for which the current clinical treatments bear dissatisfactory therapeutic effects. Biomaterial‐based strategies have been widely applied in the treatment of orthopedic diseases but are still plagued by deficient bioreactivity. With the development of nanotechnology, layered double hydroxides (LDHs) with adjustable me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 302 publications
0
7
0
Order By: Relevance
“…Environmentally-responsive 2D materials with a broad range of biomedical applications have been developed in previous studies. 17–21 For example, Shen and co-workers have shown that cobalt-molybdenum-based 2D layered double hydroxide (LDH) nanosheets (CoMo-LDH) can be used for photo-responsive dynamic therapy for cancer treatment. The CoMo-LDH nanosheets contain, by design, defects in the structure that enhance their photocatalytic and electrocatalytic activities.…”
Section: Mxenes and Targeted Deliverymentioning
confidence: 99%
“…Environmentally-responsive 2D materials with a broad range of biomedical applications have been developed in previous studies. 17–21 For example, Shen and co-workers have shown that cobalt-molybdenum-based 2D layered double hydroxide (LDH) nanosheets (CoMo-LDH) can be used for photo-responsive dynamic therapy for cancer treatment. The CoMo-LDH nanosheets contain, by design, defects in the structure that enhance their photocatalytic and electrocatalytic activities.…”
Section: Mxenes and Targeted Deliverymentioning
confidence: 99%
“…Meanwhile, layered double hydroxides (LDHs) are a type of ionic compound, consisting of stacked positively charged layers separated by interlayer anions and water molecules. LDHs are an emerging class of inorganic biomaterials with high biocompatibility and unique functions, which have garnered significant interest for in vivo application [ 12 ]. The functional versatility offers tremendous opportunities for various biomedical applications such as drug delivery and bone tissue engineering [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Among the myriad of matrixes, layered double hydroxides (LDHs, hydrotalcites) are widely selected as a two-dimensional host matrix to construct multicolor host-guest luminescent materials. [7][8][9] Hydrotalcites possesses the following advantages:…”
Section: Introductionmentioning
confidence: 99%